2005
DOI: 10.1002/eat.20105
|View full text |Cite
|
Sign up to set email alerts
|

Fear of negative evaluation and the development of eating psychopathology: A longitudinal study among nonclinical women

Abstract: The findings support a model whereby individuals with heightened fears of negative evaluation may use restrictive pathology to raise their status among peers. If this mechanism of dealing with negative evaluation fears is not sufficient in the long term, individuals may develop bulimic symptoms to deal with their negative evaluation fears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 27 publications
11
66
2
2
Order By: Relevance
“…5 A longitudinal study in women conducted by Gilbert & Meyer revealed that low SE predicted an increase in BD, and that fear of negative evaluation predicted an increase in bulimic attitudes and depression. 31 In accordance with other researchers 10,22 and considering total perfectionism (SOP and SPP), we found positive correlations between total ChEAT scores and this personality trait. Some previous studies also showed that SOP and SPP were associated with disordered eating behaviors in Portuguese adolescents 7 and young adults.…”
Section: Discussionsupporting
confidence: 92%
“…5 A longitudinal study in women conducted by Gilbert & Meyer revealed that low SE predicted an increase in BD, and that fear of negative evaluation predicted an increase in bulimic attitudes and depression. 31 In accordance with other researchers 10,22 and considering total perfectionism (SOP and SPP), we found positive correlations between total ChEAT scores and this personality trait. Some previous studies also showed that SOP and SPP were associated with disordered eating behaviors in Portuguese adolescents 7 and young adults.…”
Section: Discussionsupporting
confidence: 92%
“…It is not surprising that escape coping predicted bulimia as Heatherton and Baumeister (1991) found that bulimia is often an escape response. This result supported the findings by Gilbert and Meyer (2005) who reported that self-esteem contributed, albeit indirectly, to an increase in bulimic attitudes. In addition, this result is further confirmed by Blaase and Elklit (2001) who found that those suffering from eating disorders were more likely than those who were not to suffer from low self-esteem, utilize poor coping tactics, and have higher stress levels.…”
supporting
confidence: 91%
“…In a longitudinal study of women conducted by Gilbert and Meyer (2005), results revealed that low self-esteem predicted an increase in body dissatisfaction and that negative evaluation fears predicted an increase in bulimic attitudes and depression. This result supports the idea that with low self-esteem as a primary catalyst, followed by dissatisfaction of one's body, bulimic symptoms and/or depression can follow.…”
Section: Self-esteemmentioning
confidence: 99%
“…Because boys develop a sense of physical mastery, instrumentality, and self-determination through the process of becoming physically fit (Bas, & Donmez, 2009;Hausenblas, Cook, & Chittester, 2008;Hands et al, 2009), they may be more focused on what their bodies can do than on achieving societal appearance standards (Bers & Quinlan, 1992;Gilbert, & Meyers, 2005;Lundgren, Anderson, & Thompson, 2004) and thus view food more as fuel to help their bodies "perform" than as a source of calories that would make them fat. For example, Moy, Petrie, Dockendorff, Greenleaf, and Martin (2013) examined self-reported dietary restraint, exercise, and intuitive eating in early adolescent boys and girls.…”
Section: Although Neither Body Satisfaction Nor Self-esteem Was Assocmentioning
confidence: 99%